Pendampingan Pelaksanaan Pekerjaan Pondasi pada Mushalla Al Kautsar Desa Lambaro Skep Kota Banda Aceh - Ichsan Syahputra; Zu Irfan (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Mushalla Al Kautsar is located in Lambaro Skep Village, Banda Aceh City, where the foundation used is a well foundation type with a diameter of 0.90 m and a depth of 4.00 m, totaling 63 units. The materials used for this well foundation work were 90 cm diameter well rings, M10 type Wiremesh reinforcement steel, mountain stone, split, sand, water, and cement. A total of 10 workers were used to complete the well hole excavation work, and each well hole was completed by 5 workers per day, so the total of 63 well holes could be completed in 31 days. Meanwhile, a total of 12 workers were used to complete the well foundation casting, where each well foundation could be completed by 3 workers in 16 days. The equipment used was 1 unit Mini Mixer to mix all the concrete mortar materials, 2 units of water pumps to dry the well holes so that the concrete material would not mix with muddy water, and 4 wheelbarrows to transport the concrete mortar material from the mixing process to each well hole. Based on the results of the work, the quality achieved was in accordance with the plan, and with the number of workers available, the desired time target was met, even though there were some problems during the implementation. However, these issues were well-anticipated through the collaboration between the author and the field implementers, as well as the continuous coordination that the author maintained with the construction coordinator of Mushalla Al Kautsar.